CHILDREN'S LITERATURE: A STUDY OF POSTMODERN STYLES AND NARRATIVE TRENDS - Abdullaeva Nilufar Nasilloevna (Web of Journals Publishing, 2025)
This study provides a comprehensive analysis of the development of postmodern styles and modern narrative trends in French children's literature. The study examines examples of French children's literature from the second half of the 20th century to the beginning of the 21st century. The work examines how the main features of postmodern literature, such as the breakdown of traditional literary patterns, the disappearance of genre boundaries, metaliterary approaches, intertextuality, and the blurring of boundaries between reality and fiction, are manifested in French children's publications. According to the main conclusions of the study, modern French children's literature, while maintaining its national identity in a global cultural context, is actively adopting artistic and aesthetic strategies that reflect a postmodern worldview. As a result of such an intervention, children's literature is now becoming a multi-layered, complex, but at the same time interesting and relevant literature, aimed not only at children, but also at readers of all age groups.
Keywords: French children's literature, postmodernism, contemporary narrative styles, metaliterature, intertextuality, intergenre literature, multilayered texts, Daniel Pennac, Jean-Claude Mourlevat, Marie-Aude Murail.